Thrombolytic Agents: Nanocarriers in Targeted Release - Minghua Shen (MDPI AG, 2021)
A thrombus, known as a blood clot, may form within the vascular system of the body and impede blood flow. Thrombosis is the most common underlying pathology of cardiovascular diseases, contributing to high morbidity and mortality. However, the main thrombolytic drugs (urokinase, streptokinase, etc.) have shortcomings, including a short half-life, serious side effects and a lack of targeting, that limit their clinical application. The use of nano-drug delivery systems is expected to address these problems and a variety of approaches, including biological and physical responsive systems, have been explored. In this report, recent advances in the development of targeted nano-drug delivery systems are thoroughly reviewed.